A target concentration strategy to determine ibuprofen dosing in children. Issue 11 (25th September 2019) - Anderson, Brian J.; Hannam, Jacqueline A.
Abstract: Background: Ibuprofen is widely used for ductus arteriosus closure in premature neonates and for analgesia in children and adults. There are no maturation descriptors of clearance. This lack of maturation understanding limits dosing recommendations from premature neonates to adulthood. Methods: Published clearance estimates from different aged patients determined after administration from time‐concentration profiles were used to construct a maturation model based on size and age. Curve fitting was performed using nonlinear mixed‐effects models. A target concentration strategy was used to estimate maintenance dose at different ages. Results: There were three publications reporting an estimate of individual clearance estimates in premature neonates, three reporting population clearances in infants, 11 in children 2‐15 years (1 with individual and 9 with population clearances), and 13 adult studies (1 with individual and 12 with population clearances). Clearance maturation, standardized to a 70 kg person was described using the Hill equation. Mature clearance was 3.81 (CV 15.5%, 95%CI 3.72, 3.92) L/h/70 kg. The maturation half‐time was 36.8 (CV 9.2%, 95%CI 34.7, 40.9) weeks postmenstrual age and the Hill coefficient 11.5 (95%CI 8.1, 15). A target effect of four units (visual analogue scale 0‐10) correlated with an effect site concentration of 6.3 mg/L: a concentration achieved at trough after 400 mg 8 hourly in adults. Conclusion: Previously published pharmacokinetic parameters can be used to develop maturation models that address gaps in current knowledge regarding the influence of age on a drug's disposition. Maturation of ibuprofen clearance was rapid and was 90% of adult values by the first month of life in term neonates (ie, 44 weeks postmenstrual age) and 98% of standardized adult estimates by 3 months of age (53 weeks postmenstrual age). Clearance informed dosing predictions in all ages (premature neonate to adult) and matched those doses in common use in children older than 3 months.